Dyslipidemia among Apparently Healthy Adults in Baghdad, Iraq - Shaymaa A Naji (Journal of Global Pharma Technology, 2018)
Introduction Circulating lipids and lipoproteins are long being recognized as risk factors for developing cardiovascular diseases (CVD). Objective To evaluate the prevalence and profiles of dyslipidemia in apparently healthy (AH) and asymptomatic subjects.  Method In this cross sectional study we had randomly selected 217 AH individuals of the both the genders that were of 18- 69 years of age and disease free. Individuals having history of any medications for diabetes, hypertension and CVD were excluded from the study. The remaining healthy individuals underwent detained physical examinations and tests of lipid profiles.  Results In the overall population, the prevalence of high density lipoproteins HDL (64.5%) and very low density lipoproteins VLDL (13.8%) were most common lipid abnormalities found.  Conclusion Thus it is concluded that the AH subjects is highly susceptible to develop dyslipidemia and HDL-C abnormalities and this information could be used to design the preventive polices for future CVD events and seriously may affect the choice of AH subjects as control group in clinical researches .Keywords: Apparently healthy subjects, Lipid profile, Dyslipidemia.